Utilização de resíduos e derivados de madeira para confecção de uma guitarra elétrica - Pereira, Felipo Augusto [UNESP]; Santos, Rafael Dos [UNESP]; Campos, Cristiane Inácio de [UNESP]; Molina, Julio Cesar (My University, 2011)
The residues generation is a quite serious problem in several industrial areas and also in the lumbering area. The search for the elimination or reduction of the volume of generated residues is endless, however limited, resulting in the search for a proper destination or better use, instead of simply burning it. A lot of uses and services are commonly proposed, but with low aggregated value to the residue. This work shows the usage viability of different discarded residues and wood composites in the production of an electric guitar. Cupiúba, ipê and jatobá residues have been used besides wood composites of pinus. The residues and wood composites have shown appropriate resistance, surfacing quality and design terms, and could be used to substitute the traditionally wood used in the production of the instrument as well as in other products of similar characteristics and with larger aggregated value.
Using of the residues and wood composites for production of an electric guitar
Keywords: Electric guitar; Residues; Wood; Wood composites; Aggregated values; Industrial area; Composite materials; Musical instruments; Wood products; Combustion; Composites; Power Operated Equipment; Wood Products